Male pattern baldness is not associated with established cardiovascular risk factors in the general population - Ellis, J A; Stebbing, M; Harrap, S B (Clinical science (1979), 2001)
A number of studies have shown an association between male pattern baldness (MPB) and cardiovascular disease. Few of these studies, however, have examined whether MPB is a novel risk factor, or is associated with abnormalities of established coronary risk factors. We have therefore performed an analysis of MPB and cardiovascular risk factors in the general population. A total of 1219 male participants aged 18-70 years from the Victorian Family Heart Study were surveyed using a validated questionnaire for degree and pattern of baldness. Carefully standardized measures of height, weight, blood pressure, pulse rate, total and high-density lipoprotein cholesterol, and plasma fibrinogen were made. Subjects were grouped according to the degree and pattern of baldness as: no baldness, frontal baldness and vertex baldness. Bald men were older than non-bald men (P < 0.0001). Age was also associated with increased levels of coronary risk factors (P < 0.0001). When multiple regression was used to adjust for age differences, the levels of coronary risk factors were not significantly different between the bald and non-bald groups. The lack of association between baldness and established coronary risk factors implies that baldness may predispose to coronary heart disease through novel mechanisms yet to be defined.